Bitter Orange Aromatherapy and Its Impact on Pain Intensity Among Multigravida Women in Active First-Stage Labor - Sri Utami Subagio (STIKes Budi Luhur Cimahi, 2026)
Labor pain is a complex physiological and psychological experience that can lead to anxiety, decreased maternal cooperation, and prolonged labor if not managed properly. Non-pharmacological approaches, including aromatherapy, have become increasingly preferred due to their safety, affordability, and minimal side effects. This study aimed to determine the effect of bitter orange (Citrus aurantium) aromatherapy on reducing labor pain intensity among multigravida women during the active phase of first-stage labor at MB Eneng Nurhayati, Serang City, in 2025. This quasi-experimental research employed a nonequivalent control group design involving 22 respondents, divided equally into intervention and control groups. The intervention group received bitter orange aromatherapy through inhalation using a diffuser for 60 minutes, while the control group received standard care. Labor pain intensity was measured using the Visual Analog Scale (VAS) before and after the intervention. Exact numerical findings showed that in the intervention group (n = 11), pretest pain levels consisted of 27.3% mild pain, 54.5% moderate pain, and 18.2% severe pain, whereas posttest measurements shifted to 63.6% mild pain, 36.4% moderate pain, and 0% severe pain. Statistical analysis using the Wilcoxon Signed Rank Test indicated a significant reduction in pain intensity (p = 0.003). The mean VAS score decreased from a moderate level before the intervention to a lower, more manageable level afterward.These findings demonstrate that bitter orange aromatherapy is effective in reducing labor pain among multigravida mothers. The intervention works through olfactory stimulation of the limbic system, triggering relaxation and reducing sympathetic responses. In conclusion, bitter orange aromatherapy can serve as a practical, safe, and effective complementary therapy to support maternal comfort during childbirth and is recommended for broader application in midwifery care.